Elements of Islamic Law in Traditional Banjar Marriage "Jujuran" Viewed from a Historical Perspective - Rusdiyah, Rusdiyah; Jazila, Muhammad Afwan; Firdausi, Karunia Imam; Azmi, Muhammad; Ilmi, Muhammad Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This study examines the jujuran tradition in Banjar society, a cultural practice where the groom's family provides monetary or material gifts to the bride's family during marriage rituals. Rooted in pre-Islamic customs, jujuran persists due to its alignment with Islamic principles when practiced as a cultural tradition. Using qualitative methods, including literature review and field observations, the study highlights jujuran as a symbol of respect, wedding support, and social prestige, distinct from mahr in Islamic law. The findings underscore the significance of jujuran in fostering family bonds and preserving cultural identity amidst modern social dynamics.